Peran Pendidikan Agama Islam di Sekolah dalam Membentuk Kesadaran Kesehatan Mental Peserta Didik - Soejono, Sri Rosmalina; Iswadi, Iswadi (JOEAI (Journal of Education and Instruction), 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) in shaping mental health awareness and literacy among secondary school students. This study used a descriptive qualitative approach. The results indicate that Islamic Religious Education (PAI) learning contributes significantly to students' psychological well-being through four main mechanisms: internalization of spiritual values, strengthening the meaning of life, cultivating worship as a psychological therapy, and establishing a supportive religious environment. Values ​​such as patience, gratitude, and trust in God help students manage emotions and stress, while regular worship practices promote inner peace. Islamic Religious Education (PAI) teachers also act as spiritual counselors, fostering a sense of security and empathy in the learning environment. In conclusion, Islamic Religious Education (PAI) teachers play a crucial role in shaping students' mental health awareness and literacy.   Keywords: Spiritual Awareness, Mental Health, Psychological Well-Being, Islamic Religious Education, Students